Pancasila Education as an effort to strengthen students’ national identity - Nisa', Isma Mutia Khoirun (Maliki Interdisciplinary Journal, 2025)
Pancasila is the foundation of our country which is the umbrella and source of law as well as a source of inspiration in national life. National Identity is a construction agreed upon by the nation's citizens as a symbol of identification. As a national identity, Indonesia has various national identities represented in several forms, one of which is the national language or unifying language, namely Indonesian. National identity refers to the personality or identity of a nation that distinguishes it from other nations. In the context of a nation, national identity is more related to culture, customs, and distinctive characters. Civic education helps students develop positive attitudes such as self-confidence, courage, cooperation, and discipline.